VD_FINDINFO Faillite / 2018 / 10 vom 27. April 2018 - VD Tribunal cantonal (2018)
OUVERTURE DE LA FAILLITE, MAXIME INQUISITOIRE, INSOLVABILITÉ, PAIEMENT | 174 al. 1 LP, 174 al. 2 LP, 174 LP, 255 let. a CPC (CH)